E-Court Management System for Mahkamah Sesyen and Magistrate lpoh - Omar, Abdul Aziz (Universiti teknologi petronas, 2008)
In this project paper, the Court Management System project is still under planning phases where the objective and the scope of the project has been design. E-Court Management System is web based system that integrates four components which is Content Management Service, Contact Management Service, Case Management System and Transaction Service. With the objective and scope has been define, the development of this project can continue with analysis phases and development phases. The requirement of the project also being define on the project to make sure it comply with the objective, scope and project development life cycle. This website system include all five project development life cycle because it consider as critical website system. The five project development life cycle is initiation and feasibility study, planning, analysis, design and development and the last one is testing and implementation. In each phase, there were several steps taken according to few methodologies to achieve the objective of the phase. The result of this project soon will be a fully functioning E-Court Management System according to the new business flow which meet the objective of the project and solve the problem in existing system as well.